2021
DOI: 10.3390/agriculture11060560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Organic Fertilizers on Improving Soil from Newly Reclaimed Land to Crop Soil

Abstract: The rapid development of cities in the recent 10 years caused a reduction in the cultivated land area, which only accounts for 14% of the total land area in China. Land development and reclamation have been regarded as an effective way to compensate farmland occupation. However, most of the newly reclaimed land has poor soil fertility and suitability; in some cases, the production capacity is only 10–30% of the occupied farmland. In order to ameliorate the soil quality of the newly reclaimed land, this study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 29 publications
9
43
0
Order By: Relevance
“…Furthermore, the result of this study showed that there was a complex relationship between soil parameters and plant/microbial growth and soil nutrient elements because there was a differential change between the disease alone and in combination with either CF or OF in the contents of available soil nutrient elements, such as the content of alkalihydrolyzable nitrogen, exchangeable calcium, available phosphorus and exchangeable magnesium in bayberry rhizosphere soil. In agreement with the result of this study, the growth of soil microbe is affected by a lot of environmental factors such as soil pH and organic matter as well as the content of exchangeable magnesium, nitrogen, available phosphorus and exchangeable calcium [53].…”
Section: The Effect Of Compound/bio-organic Fertilizer On Rda Of Soil Properties and Microbial Communitiessupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the result of this study showed that there was a complex relationship between soil parameters and plant/microbial growth and soil nutrient elements because there was a differential change between the disease alone and in combination with either CF or OF in the contents of available soil nutrient elements, such as the content of alkalihydrolyzable nitrogen, exchangeable calcium, available phosphorus and exchangeable magnesium in bayberry rhizosphere soil. In agreement with the result of this study, the growth of soil microbe is affected by a lot of environmental factors such as soil pH and organic matter as well as the content of exchangeable magnesium, nitrogen, available phosphorus and exchangeable calcium [53].…”
Section: The Effect Of Compound/bio-organic Fertilizer On Rda Of Soil Properties and Microbial Communitiessupporting
confidence: 91%
“…Furthermore, the result of this study showed that there was a complex relationship between soil parameters and plant/microbial growth and soil nutrient elements because there was a differential change between the disease alone and in combination with either CF or OF in the contents of available soil nutrient elements, such as the content of alkalihydrolyzable nitrogen, exchangeable calcium, available phosphorus and exchangeable magnesium in bayberry rhizosphere soil. In agreement with the result of this study, the growth of soil microbe is affected by a lot of environmental factors such as soil pH and organic matter as well as the content of exchangeable magnesium, nitrogen, available phosphorus and exchangeable calcium [53]. Furthermore, the result of this study showed that there was a complex relationship between soil parameters and plant/microbial growth and soil nutrient elements because there was a differential change between the disease alone and in combination with either CF or OF in the contents of available soil nutrient elements, such as the content of alkalihydrolyzable nitrogen, exchangeable calcium, available phosphorus and exchangeable magnesium in bayberry rhizosphere soil.…”
Section: The Effect Of Compound/bio-organic Fertilizer On Rda Of Soil Properties and Microbial Communitiessupporting
confidence: 91%
“…Immature soil is not suitable for plant growth, but it can be modified by adding organic matter and PGP microbes to promote soil maturity and plant growth [1][2][3]. However, little attention has been paid to the effect of PGP microbes on plant growth promotion in immature soil.…”
Section: Discussionmentioning
confidence: 99%
“…The immature soil in developed land is not suitable for plant growth because it does not have enough time to develop via normal soil-forming processes. In most instances, the soil is acidic and poor in nutrients with a high gravel content [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been well documented that the growth of soil microbes is affected by a series of environmental factors such as soil pH, organic matter and magnesium content, as well as available nitrogen, phosphorus and calcium [29,30]. Furthermore, the results of this study revealed the complexity of the relationship between microbial growth and soil nutrient elements due to the fact that a differential change was observed between diseased and healthy bayberry rhizosphere soil in the contents of available soil nutrient elements, such as available nitrogen, calcium and phosphorus, as well as the magnesium content; indeed, nutritional balance may be best for microbial growth.…”
Section: Soil Propertiesmentioning
confidence: 99%